PEMBERIAN BEBERAPA DOSIS TRICHOKOMPOS AMPAS TAHU TERHADAP PERTUMBUHAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Krisman '; Fifi Puspita; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Oil palm plantations (Elaeis guineensis Jacq.) is an important commodity in Indonesia which is constantly increasing both in land area and its production. The increase in land requires a qualified oil palm seedings. One of the appropriate measures to obtain quality seed is by giving organic fertilizer, such as Trichocompost tofu dregs. The research aimed to determine the effect of several doses of Trichocompost tofu dregs and to obtain the best dose for the growth of oil palm in main nursery. The research was conducted at the experimental farm, Technical Implementation Unit, Faculty of Agriculture, University of Riau. The research started from April to August 2015. The research was conducted experimentally by using completely randomized design (CRD) which consist of 5 treatment and 4 replication then obtained 20 experiment units. Each of the experiment unit consisted of 2 seeds, so it obtain 40 seeds. The treatment tested was giving Trichocompost tofu dregs dose 0 g/plant, 75 g/plant, 150 g/plant, 225 g/plant, and 300 g/plant. The data was analyzed statistically and followed by DNMRT further test at 5% level. Parameters measured was increase of high, increase of stump diameter, increase of midrib number, root volume, and dry wight. The result showed that giving Trichocompost tofu dregs dose 225 g/plant give the best effect on the growth of oil palm in main nursery. Keywords : Oil palm, main nursery, Trichocompost tofu dregs.